The Economic Security of Russia: a New Look - Vladimir Alexandrovich Shamakhov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article provides a review of monograph of M.I. Krotov and V.I. Muntiyan “Economic security of Russia: System sing content and ways of ensuring economic security of Russia.